Analysis of Teacher Difficulties in Teaching Vocabulary at Elementary School - Gulo, Sri Mawarni Nofitri (Progressive of Cognitive and Ability, 2024)
This research aims to determine teachers' difficulties in teaching vocabulary elementary school. The scope of the research only focuses on describing or explores the difficulties teachers face in teaching English vocabulary. This study used descriptive qualitative method. The subjects of this research are 2 English Teacher at State Elementary School. This research uses interviews to collect data. Based on the results of research data analysis, it was concluded that teacher Difficulty in teaching vocabulary is difficulty in choosing the vocabulary to be taught because there are many words in English and students don't have the same words ability, difficulty in applying teaching techniques or presenting new vocabulary. Students don't pay attention teacher explanations, noisy, and passive students in vocabulary learning. And teachers find it difficult to review or evaluate students understanding of the words that have been taught because students do not still understand the meaning of the vocabulary